The Use of ZrO2 Waste for the Electrolytic Production of Composite Ni–P–ZrO2 Powder - Jolanta Niedbała (MDPI AG, 2021)
Ni–P–ZrO2 composite powder was obtained from a galvanic nickel bath with ZrO2 powder. Production was conducted under galvanostatic conditions. The Ni–P–ZrO2 composite powder was characterized by the presence of ZrO2 particles covered with electrolytical nanocrystalline Ni–P coating. The chemical composition (XRF method), phase structure (XRD method) and morphology (SEM) of Ni–P–ZrO2 and the distribution of elements in the powder were all investigated. Based on the analyses, it was found that the obtained powder contained about 50 weight % Zr and 40 weight % Ni. Phase structure analysis showed that the basic crystalline component of the tested powder is a mixed oxide of zirconium and yttrium Zr0.92Y0.08O1.96. In addition, the sample contains very large amounts of amorphous compounds (Ni–P). The mechanism to produce the composite powder particles is explained on the basis of Ni2+ ions adsorption process on the metal oxide particles. Current flow through the cell forces the movement of particles in the bath. Oxide grains with adsorbed nickel ions were transported to the cathode surface. Ni2+ ions were discharged. The oxide particles were covered with a Ni–P layer and the heavy composite grains of Ni–P–ZrO2 flowed down to the bottom of the cell.